On solving the plateau problem in parametric form - Baruch cahlon; Alan D. Solomon; Louis J. Nachman (International Journal of Mathematics and Mathematical Sciences)
This paper presents a numerical method for finding the solution of Plateau's problem in parametric form. Using the properties of minimal surfaces we succeded in transferring the problem of finding the minimal surface to a problem of minimizing a functional over a class of scalar functions. A numerical method of minimizing a functional using the first variation is presented and convergence is proven. A numerical example is given.